(untitled) (Baghdad Science Journal, 2024)
In this paper, a study of monocalcium phosphate production based on extractable phosphoric acid obtained from Central Kyzyl-Kum phosphorites was conducted. Effects of various parameters (density, temperature, and viscosity of starting materials) on the process of defluoridation and desulfation of extraction phosphoric acid and production of monocalcium phosphate based on calcium carbonate were studied. The experiments were mainly conducted on two samples, and the composition of the substances before and after the process was studied. According to the results, the contents of other components also increase proportionally (sample 1). Thus, the content of calcium oxide increases from 1.58% to 5.54% with a content of 60% P2O5, magnesium from 0.49% to 1.15%, iron oxide from 0.25% to 0.85%, aluminum oxide from 0.38% to 1.24%, sulfate ions from 0.23% to 0.76%, the content of calcium oxide increases from 2.09% to 7.40% with a content of 60% P2O5, magnesium from 0.80% to 2.83%, iron oxide from 0.25% to 0.90%, aluminum oxide from 0.38% to 1.34%, sulfate ions from 0.23% to 0.82%. The fluorine content decreases from 0.32% to 0.17% depending on the EPA concentration (sample 2). Some factors, such as the rate and concentration of phosphoric acid and high-speed separation of phosphoric acid, were also studied in the process of obtaining monocalcium phosphate and its chemical composition and properties. The results obtained based on both samples were studied and analyzed using X-ray, IR spectrum, scanning electron microscopic, and elemental analysis.